Knowledge Gaps and Self-Care Challenges Among Elderly Hypertensive Patients: Barriers, Influencing Factors, and the Need for Adaptive Interventions - Suharyanti, Bernadhea Agnes; Pujiastuti, Theresia Tatik; Nekada, Cornelia Dede Yoshima (Care : Jurnal Ilmiah Ilmu Kesehatan, 2025)
Hypertension, a non-communicable disease often called the "silent killer," affects 30.8% of Indonesians aged 18 and older, with 34% of those over 60 undiagnosed (2023 Indonesian Health Survey). The high prevalence among the elderly is frequently associated with inadequate self-care activities. This study aims to find the relationship between hypertension knowledge and self-care activities among the elderly with hypertension at a Public Health Center Depok III in Sleman. A descriptive-quantitative approach with a cross-sectional design was used. 80 elderly with hypertension were selected using purposive sampling. Inclusion criteria were being over 60 years old, compos mentis, and able to communicate verbally; exclusion criteria included sudden illness or urgent commitments preventing questionnaire completion. Hypertension knowledge was measured with the Hypertension Knowledge Level Scale (HK-LS) instrument, and self-care activity was assessed using the Hypertension Self-Care Activity Level Effects (H-SCALE) instrument. The Gamma test showed a significant, positive, and very strong relationship between the knowledge level and self-care activity among the elderly with hypertension, with a p= 0.043 (r =0.875). The results indicated that there is a significant, positive, and very strong relationship between the knowledge level and self-care activity among the elderly with hypertension at a Public Health Center Depok III in Sleman. Based on the findings of this study, it is recommended that the health center improve its educational program, particularly concerning a low-salt diet, physical activity, and weight management.